Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# A solution $\left( {x,y} \right)$ of the system of equations $x - y = \dfrac{1}{3}$ and ${\cos ^2}\left( {\pi x} \right) - {\sin ^2}\left( {\pi y} \right) = \dfrac{1}{2}$ is given byA) $\dfrac{2}{3},\dfrac{1}{3}$B) $\dfrac{7}{6},\dfrac{1}{6}$C) $\dfrac{{13}}{6},\dfrac{{11}}{6}$D) $\dfrac{1}{6},\dfrac{5}{6}$

Last updated date: 11th Sep 2024
Total views: 429.6k
Views today: 6.29k
Verified
429.6k+ views
Hint:
To solve this we can use the formula ${\cos ^2}A - {\sin ^2}B = \cos \left( {A + B} \right).\cos \left( {A - B} \right)$. Here $A = \pi x$ and $B = \pi y$. So $A - B$ will be $\pi \left( {x - y} \right)$ substitute the value of $x - y = \dfrac{1}{3}$ in this. In this way you will obtain the value of $\cos \left( {A + B} \right)$. Use $\cos \left( {A + B} \right)$ function to arrive at the correct answer among the given options.

Complete step by step solution:
Given: $x - y = \dfrac{1}{3}$,
${\cos ^2}\left( {\pi x} \right) - {\sin ^2}\left( {\pi y} \right) = \dfrac{1}{2}$
We know that ${\cos ^2}A - {\sin ^2}B = \cos \left( {A + B} \right).\cos \left( {A - B} \right)$ assuming $A = \pi x$ and $B = \pi y$ we get
${\cos ^2}\left( {\pi x} \right) - {\sin ^2}\left( {\pi y} \right) = \cos \left( {\pi x + \pi y} \right)\cos \left( {\pi x - \pi y} \right) \\ \Rightarrow \dfrac{1}{2} = \cos \left[ {\pi \left( {x + y} \right)} \right]\cos \left[ {\pi \left( {x - y} \right)} \right] \\ \Rightarrow \dfrac{1}{2} = \cos \left[ {\pi \left( {x + y} \right)} \right]\cos \left[ {\pi \left( {\dfrac{1}{3}} \right)} \right] \\ \Rightarrow \cos \left[ {\pi \left( {x + y} \right)} \right] = \dfrac{1}{{\dfrac{2}{{\cos \dfrac{\pi }{3}}}}} = \dfrac{1}{{\dfrac{{\dfrac{2}{1}}}{2}}} = 1 \\ \Rightarrow \cos \left[ {\pi \left( {x + y} \right)} \right] = 1 \\$
Let $x + y = n$
Then $\cos n\pi = 1$
$x - y = \dfrac{1}{3}$ (where $n$ is an integer)
$\Rightarrow 2x = 2n + \dfrac{1}{3} \\ \Rightarrow x = \left( {n + \dfrac{1}{6}} \right) \\ \Rightarrow y = 2n - x = 2n - n - \dfrac{1}{6} \\ \Rightarrow y = n - \dfrac{1}{6} \\$
Putting
$\left( {x,y} \right) = \left( {x,y} \right) \equiv \left( {\dfrac{1}{6}, - \dfrac{1}{6}} \right) \\ n = 1 \\ \Rightarrow \left( {x,y} \right) = \left( {\dfrac{4}{6},\dfrac{5}{6}} \right) \\ n = 2 \\$
$\Rightarrow \left( {x,y} \right) \equiv \left( {\dfrac{{13}}{6},\dfrac{{11}}{6}} \right)$ (Only this option matches)

The correct answer is option (c) $\left( {\dfrac{{13}}{6},\dfrac{{11}}{6}} \right)$

Note:
In multiple questions like these it might not be possible to obtain the correct solution only from the question. You may require to analyze the options to arrive at the correct answer. Similar questions might be asked that requires the knowledge of other trigonometric equations.